Resiliensi Masyarakat Di Relokasi Hunian Tetap Siosar Pasca Erupsi Gunung Sinabung Kabupaten Karo - Benny Antony Kaban; Eko Teguh Paripurno; Puji Lestari; Yohana Noradika Maharani; Johan Danu Prasetya; Ficky Adi Kurniawan (Asosiasi Riset Ilmu Teknik Indonesia, 2023)
Indonesia is one of the countries that has a fairly high level of natural disaster vulnerability. Mount Sinabung is a strato-type volcano. Administratively, Mount Sinabung is in the Karo Regency, North Sumatra. The eruption of Mount Sinabung has had a very significant physical, psychological and social impact on society. In facing a disaster, survivors need to survive and continue living. The ability to adapt to conditions after experiencing a traumatic event is called resilience. People who lost their homes due to the eruption of Mount Sinabung must be willing to be relocated to new, safer places such as permanent Shelter. Researchers want to see how disaster survivors in the Siosar Permanent Residence respond to being able to recover or recover from their previous situation. The method used in this research is descriptive qualitative with a case study approach. Data collection techniques were carried out using interviews/FGD, observation and documentation studies. The research results show that there are still teenagers who are not yet fully resilient. Researchers found teenagers who have not been able to recover from the problems they faced after the eruption of Mount Sinabung. Therefore, support from various parties or the pentahelix (government, academics, business world, society and mass media) is needed to build sustainable resilience in Siosar Permanent Shelter.